Analysis of Factors Affecting Electricity Sales at PLN ULP Medan Timur - Morina Sari Simamora; Saparuddin Siregar (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
This study aims to find out how to promote, market and what factors are influenced in the sale of PLN ULP Medan Timur, the results of this study are sales factors that affect according to customer needs in electronic fulfillment, climate change, changes in the status of houses turning into businesses and development. house or building along with discounts given to customers. This study uses qualitative research by collecting data and interviews with employees of PLN ULP Medan Timur. This study provides results for an assessment of promotions in using the right time and cashback that customers get with the promotions given. PLN ULP Medan Timur uses a way to get to know customers closely to provide information about promotions and discounts that customers need for business and industry.